Feasibility of distance-monitoring on sedentary time and physical activity among Sri Lankan adolescents - Wickramarachchi, W Kankanamalage Dona Shashini Anushka (2022)
COVID-19 restrictions such as the closure of schools and parks, and the cancellation of youth sports and activity classes around the Sri Lanka may prevent children from achieving recommended levels of physical activity (PA). The study was carried out during the COVID 19 pandemic in Sri Lanka and it took into considerations factors such as physical activity level (PA level), sedentary behaviour (SB), behavioral sleep problems (BSP) and body mass index (BMI). The prime aim of this study was to examined the feasibility of distance-monitoring concept on sedentary time (ST) and PA of Sri Lankan adolescents. Along four minor objectives were to assess the current status of PA and ST, find the effectiveness of distance monitoring program on PA and ST, find the relationship between to PA, ST, BSP, BMI and finally compare the differences of PA, ST BSP and BMI among gender. Study was conducted by using concurrent triangulation design under the mixed method research approach. Data were obtained from 347 male and female adolescents aged between 13-17 years old in the year 2020 and 2021 from four provinces in Sri Lanka by using multi stage sampling technique. Data were obtained from WHO STEPS instrument for PA and Adolescent Sedentary Activity Questionnaire (ASAQ) for ST. Parents also reported children BSP through Children’s Sleep Habits Questionnaire (CSHQ). Additionally, participants were recorded their usual daily activities in a given diary template which include PA, BSP and other activities over a two months’ (2) period. Main outcome was to assess the feasibility of the distance monitoring programme defined as recruitment and retention >70% and treatment fidelity of >80% of distance monitoring programme. A total of 500 participants were invited to participate, 420 adolescents met eligibility criteria, and were recruited. At follow-up, the overall retention of participants was 347 (82.6%) and treatment fidelity rate was 87.5%. The study found that PA level of the respondents increased significantly from 784.7 MET/min per week to 831.7 MET/min per week (p<0.05). The ST also decreased significantly from 3490 min/per week to 3332 min/per week (p<0.05). Educational time and cultural time of adolescents were highly correlated with total sedentary time. There is no positive relationship between PAL, BSP and BMI. However, there is a positive relationship between ST and BMI. Our findings also showed 34% of adolescents were suffering from sleeping problems. The study also showed that 66% of adolescents adhered to the recommended guidelines using distance monitoring. According to the thematic analysis students and teachers’ perception on this was an even chance to accept this distance monitoring concept among the adolescents in Sri Lanka. Parents seems to thinks its impractical and it’s a quite challenge to implement. Hence, distance monitoring has potentials in regulating and decreasing (SB) among adolescents in Sri Lanka and its feasible. Future research is recommended to help develop better and effective guidelines on distance monitoring to decrease SB especially during the COVID 19 pandemic in Sri Lanka.